2017
DOI: 10.1159/000453334
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Nitrosative Stress in Children with Chronic Spontaneous Urticaria

Abstract: Background: Chronic spontaneous urticaria (CSU) is an idiopathic condition that seriously affects quality of life. It is well known that oxidative stress and nitrosative stress (NS) are generally involved in many chronic inflammatory diseases. This study aimed to evaluate the possible role of NS in the pathogenesis of CSU. Methods: Thirty-two children with CSU and 22 healthy control subjects were enrolled in the study. Demographic and clinical features were defined, and disease activity was quantified using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…As blood levels of NO x and nitrate are significantly higher in CSU patients compared to healthy controls, and correlate with disease activity, a pathogenic role of nitrosative stress has been suggested [64]. A recent study reported a frequent association of CSU with upper gastrointestinal inflammatory disorders with and without Helicobacter pylori infection, and an improvement of urticaria in parallel with a successful treatment of the gastrointestinal disorder [65].…”
Section: Unraveling Urticariamentioning
confidence: 99%
“…As blood levels of NO x and nitrate are significantly higher in CSU patients compared to healthy controls, and correlate with disease activity, a pathogenic role of nitrosative stress has been suggested [64]. A recent study reported a frequent association of CSU with upper gastrointestinal inflammatory disorders with and without Helicobacter pylori infection, and an improvement of urticaria in parallel with a successful treatment of the gastrointestinal disorder [65].…”
Section: Unraveling Urticariamentioning
confidence: 99%